After hours redemption - Alexander, Kianna (Alexander, Kianna. 404 Sound., 2020)
"Songwriter Eden Voss had the perfect man--sexy, charming, talented and hers. Until record executive Blaine Woodson broke her heart to save his fledging label. Now music's bad boy is back, begging for her songwriting skills in his studio...and her lovemaking skills after hours. Eden vows to keep things strictly business this time. But there is nothing professional about the heat still between them..."--Back cover.